Integrated Management of Jassid in Groundnut (Journal of Environmental Science and Natural Resources, 2015)
Management of Jassid (Empoasca terminalis) of groundnut using botanical and chemical insecticide viz. zet powder, neem kernel extract, biskatali dust extract and neem oil, Tafgar 20 EC and their integration was studied at Regional Agricultural Research Station, .Bangladesh Agricultural Research Institute, Rahmatpur, Barisal during rabi season of 2008-2009 and 2009-2010. The infestation of Jassid (Empoasca terminalis) was noticed during 1st week of March and the highest infestation of Jassid (Empoasca terminalis) was 345 per plant observed in the last week of April in 2009, 2010. Among the treatments as expected Tafgar 20 EC reduced the highest Jassid (Empoasca terminalis) (99.55%) with the highest BCR (5.65) followed by Neem kernel extract + Zet powder (56.32%), Neem oil + Zet powder (55.13%). Neem kernel extract (2.5%) + Biskatali dust extract (54.31) and Zet powder (48.33%) recorded at 15 days after spray over the pre-treatment count. Neem kernel extract + Zetpowder gave the second highest BCR (4.76) followed by Neem oil +Zet powder (4.29), Neem kernel extract (2.5%) + Biskatali dust extract (3.88) and Zet powder 4g/l of water (3.32).DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22222 J. Environ. Sci. & Natural Resources, 7(2): 137-140 2014